2022
DOI: 10.1021/acs.biomac.2c00201
|View full text |Cite
|
Sign up to set email alerts
|

Edge-On (Cellulose II) and Face-On (Cellulose I) Adsorption of Cellulose Nanocrystals at the Oil–Water Interface: A Combined Entropic and Enthalpic Process

Abstract: Nanocelluloses can be used to stabilize oil–water surfaces, forming so-called Pickering emulsions. In this work, we compare the organization of native and mercerized cellulose nanocrystals (CNC-I and CNC-II) adsorbed on the surface of hexadecane droplets dispersed in water at different CNC concentrations. Both types of CNCs have an elongated particle morphology and form a layer strongly adsorbed at the interface. However, while the layer thickness formed with CNC-I is independent of the concentration at 7 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The experimental data closely matched the estimations based on vOCG theory. The absolute values of the W ad indicating CNF desorption from the hexadecane–water interface (28.2 mJ m –2 ) are also close to the simulation result of Gibbs free energy variation in adsorption of CNC to the heptadecane–water interface reported by Haouache et al (−26 ± 7 mJ m –2 ) …”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The experimental data closely matched the estimations based on vOCG theory. The absolute values of the W ad indicating CNF desorption from the hexadecane–water interface (28.2 mJ m –2 ) are also close to the simulation result of Gibbs free energy variation in adsorption of CNC to the heptadecane–water interface reported by Haouache et al (−26 ± 7 mJ m –2 ) …”
Section: Resultssupporting
confidence: 88%
“…Figure 3 shows a Pickering emulsion stabilized by an aqueous dispersion containing 0.10 wt % ACC-BCNFs. The appearance (Figure 3) and significant increase in transparency (Table S8 56 Only the nitrobenzene result having a W ad value closest to 0 differed from the predicted behavior. This mismatch was presumably owing to the influence of the amphiphilic structures of the CNF films prepared from CNF-stabilized oil droplets.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Pickering emulsion is an oil–water stabilization system, in which the surfactant is creatively replaced by solid particles. It can be used to load external healing agents to assist in the healing of hydrogels . As Xu et al reported, a linseed oil (LO)-in-water Pickering emulsion stabilized by sulfated cellulose nanocrystals (CNCs) and octylamine-modified CNCs can be used in a vanish to realize self-healing performance after scratching as a result of the reaction of the LO with oxygen .…”
Section: Introductionmentioning
confidence: 99%